The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.bjane.2013.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Association of clonidine and ropivacaine in brachial plexus block for shoulder arthroscopy

Abstract: The use of brachial plexus block with local anesthetic for analgesic postoperative control is well established in the literature. The addition of clonidine in the dose proposed for prolongation of the analgesic effect and reduction of opioid rescue proved unhelpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…in two different studies found clonidine reduced PONV in an appreciable manner by an opioid-sparing effect. [ 27 28 ] In our study, we had similarly found less nausea, vomiting, shivering in clonidine-treated group.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…in two different studies found clonidine reduced PONV in an appreciable manner by an opioid-sparing effect. [ 27 28 ] In our study, we had similarly found less nausea, vomiting, shivering in clonidine-treated group.…”
Section: Discussionsupporting
confidence: 74%
“…Similar findings were evidenced by Faria-Silva et al ., who conducted shoulder arthroscopic surgeries under brachial plexus block and found clonidine mixed local anesthetic group asked for morphine as rescue analgesic much later and in lesser amount. [ 27 ] Gupta et al . also demonstrated similar findings while clonidine was used in epidural route for knee replacement surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…To describe higher pain levels, the scales used 14 different anchors in total ( Figure 2 ) with “worst pain imaginable” [ 11 , 12 , 15 , 26 , 36 , 38 , 43 , 48 , 51 , 54 ] being the preferred anchor. The second most frequent anchor was “worst pain” [ 10 , 28 , 33 , 34 ] and then successively “most severe pain imaginable” [ 19 , 20 , 37 ], “severe pain” [ 18 , 32 , 46 ], and “worst possible pain” [ 29 , 41 , 47 ]. Twelve studies did not report the used anchors [ 13 , 16 , 17 , 27 , 31 , 35 , 40 , 49 , 50 , 55 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies used more than one method due to variations in analgesic protocols, such as different scheduled analgesics and rescue analgesics. In most cases, only the rescue analgesics were recorded (in mg or number of doses) [ 14 , 21 , 24 , 47 , 49 ], or the number of patients requesting [ 34 , 54 , 56 ] (or not requesting) analgesics [ 19 ]. For patients using patient-controlled analgesia (PCA, usually with intravenous opioid), the number of attempts, number of doses, and/or cumulated dose (for example during 24 hours) were reported [ 31 , 37 , 41 , 48 , 50 , 52 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation